2017
DOI: 10.1016/j.eats.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Inlay Osteochondral Reconstruction: Arthroscopic One-Step Osteochondral Lesion Repair in the Knee Using Morselized Bone Grafting and Hyaluronic Acid-Based Scaffold Embedded With Bone Marrow Aspirate Concentrate

Abstract: Cartilage injury of the knee that is associated with significant subchondral bone loss can result in great morbidity, and treatment options that provide durable repair are limited. Osteochondral autograft and allograft reconstruction of these lesions has been used extensively; however, these techniques often require a more invasive surgical exposure, and restoring the natural articular surface radius of curvature can be challenging, particularly in larger lesions. Cell-based repair of these lesions, using auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Open techniques are preferred because they are time saving and the lesions can be easily assessed. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Open techniques are preferred because they are time saving and the lesions can be easily assessed. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a number of studies have reported concomitant procedures, such as abrasion arthroplasty (Beckmann et al, 2015), autologous bone grafting to restore bone mass (Sadlik et al, 2017), treatment of co-existing pathologies (Wong et al, 2013), and BMS (Jin et al, 2011), PRP (Broeckx et al, 2019a) and HA (Charlesworth et al, 2019) to repair cartilage defects. Thus, the abovementioned methods are recommended to supplement PBSCs for cartilage repair and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Although suture may be used to stabilize the graft during open techniques, fibrin glue has been shown to increase the stability of fixation of type I/III collagen patches, 10 and we have used fibrin glue routinely to secure scaffolds after arthroscopic implantation with excellent results. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in cell-based cartilage repair techniques that use dry arthroscopic methods have further advanced this field, given the advantages of a minimally invasive technique that reduces morbidity and optimizes postoperative rehabilitation progression. 7 , 8 This Technical Note describes a method of cell-based cartilage repair using allogeneic MSCs sourced from Wharton's jelly (WJ-MSCs) that are embedded onto a type I/III collagen scaffold and implanted under dry arthroscopy ( Video 1 ).…”
mentioning
confidence: 99%